From the status of the person in Rome to the evolution of human rights - Oyarce-Yuzzelli, Aarón (2011)
This article will deal with the concept of person in Roman law, from its beginning with the nasciturus, concentrating on the status of the person, both social, civitatis, familial, libertatis, as well as a study of existing legal or moral persons. . In addition, we will analyze the concept of person in comparative law and we will make an analogy with the right of persons in national legislation. The German pandectist school regarding the concept of person, points out that the concept is vitiated from the root, with each moral and legal construction created. The historically determined person; instead concrete individuality, it is transferred to the plane of empiricism or relativity, then it is reduced to an abstraction, or turned into a fantastic subject. But natural law is historically the right of the person, as a concrete and defined individual, not an irrelevant atom, or a doll made to be exorcised.